Factors influencing on familys debt of civil servants in Bangkok and metropolitan area - Somjai Chounlakorn; Nomchit Kittichotipanit (My University, 2016)
บทคั ดย องานวิ จั ยนี ้ มี วั ตถุ ประสงค เพื ่ อศึ กษาป จจั ยที ่ มี อิ ทธิ พลต อการมี หนี ้ สิ นของครอบครั วข
Keywords: Civil servants; Housing, Finance, and Neoliberalism